The Study of Correlations of Clinical Services Process, Clinical Environment, and Clinical Services Satisfaction at Pediatric Clinics in Nan - Vanakornkul, Korrakot (Huachiew Chalermprakiet Law Journal, 2025)
This research objective is to study satisfaction of patients’ parents on clinical services at the pediatric clinics in Nan province, Thailand. The researcher collected data from patients’ parents instead of the patients because patients in pediatric clinics are kids or children, and their parents are decision makers in selecting which Pediatric clinics are appropriate for their children. Random sampling was used in the data collection. Only 112 informants who experienced pediatric clinical services were willing to complete the survey questionnaires. The quantitative research methodology was conducted in this study. The set of questionnaires was distributed to collect data related to clinical services process, clinical environment, and clinical services satisfaction. The data gathered were analyzed using descriptive statistics and Structural Equation Modeling (SEM). The research findings indicate that both factors-clinical services process and clinical environment significantly have positive relationships with clinical services satisfaction.